Dirāsah Tajrībiyyah Muqāranah baina Istikhdām Wordwall wa Quizlet fī Itqān al-Mufradāt li-Ṭullāb al-Madrasah al-Mutawassiṭah - Jannah, Nisa Miftahul; Inayah, Inayah; Sutiyono, Agus (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study aims to compare the effectiveness of two widely used digital learning platforms, Wordwall and Quizlet, in improving Arabic vocabulary mastery among seventh-grade students at MTs Ar-Rois Cendekia Semarang City. Employing a quantitative approach with a quasi-experimental design using a non-equivalent control group, the research involved two experimental classes consisting of 44 students selected through purposive sampling. Data collection employed vocabulary tests, observations, and documentation. The instruments were validated through validity and reliability testing, followed by data analysis using the Mann–Whitney U test, as the normality test indicated that the data were not normally distributed. The results showed that there was no statistically significant difference between Wordwall and Quizlet in improving students’ Arabic vocabulary mastery (p = 0.317 > 0.05), with a small effect size (r = 0.169), indicating that both platforms have comparable effectiveness in supporting vocabulary learning.